Propuesta de inversión para la producción y comercialización de una bebida energizante natural elaborada a base de pitahaya año 2012 - Bastidas Riofrío, Carlos Manuel (2013)
The present study is Arenillas geographical setting, which are based around families of farmers engaged in cultivation. The aim of the study is to identify market opportunities and establish the financial feasibility of a project for the implementation of a cactus flower company in the area of influence.For the market study, we selected a representative sample, in which we investigated issues related to advertising, to consume if based rehydration drink pitahaya, knowledge and identification of organic products, use interest and other related services to agricultural activity in the area.In terms of financial feasibility, analysis was performed on the size and location of the service, administration, engineering, project costs and revenues, breakeven determination, analysis and financing of investments, and financial evaluation company. Among the most important results are most relevant identification through cash flow NPV obtained with which we measure the profitability of the project resulting in a positive response because it is feasible, since this value is greater than zero. These results were projected to 5 five years earning substantial profits, which will cover the costs of the organization and shall comply with the returns required by investors. It was also considered a risk analysis, which was satisfactory, so that measured changes and impacts that will result in cash flow over a period of five years, in this analysis includes the optimistic scenario, pessimistic and expected. The advantage of this analysis is that we can make decisions early.